Regional Policy in the Southern African Development Community - J. Ernst Drewes; Mariske van Aswegen (Routledge, 2024)
This book analyses regional development policy or the lack thereof in the Southern African Development Community (SADC), which forms a key trading bloc on the African continent as well as the Global South. It explores the main attributes relevant to the formulation of regional policy in terms of socio-economic policies as well as spatial planning instruments. Further, it integrates macro and sectoral policy frameworks and applies the goals and objectives thereof practically through the appropriate and timely application of spatial targeting instruments within the SADC as a developing region. The focus of the research is to reflect on the social, economic, environmental, and political arguments through a focused analysis of relevant planning instruments, policies, and barriers in terms of the regional policy goals for the SADC region. The book provides insight into the role of the SADC in the context of regional development, analyses regional policy on a national, regional, and continental scale with reference to the SADC, and evaluates the inherent potential in the regional economy as well as barriers to regional development. It identifies gaps in the existing regional policy framework of the region and its constituent members and makes recommendations for improved regional policy frameworks and their implementation. The book is targeted at scholars, researchers, and students studying international trade as well as regional and economic development, and urban and regional planning and policy. It will also be a useful resource for policymakers, as it provides practical policy guidelines for improved regional planning towards a comprehensive regional policy framework. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.
Keywords: 320; Southern African Development Corridor; spatial integration; regional policy; trading blocs; regional integration; developing countries; Southern African Development Community